The concept of integrated architectural and urban planning support for socio-biospheric development (on the example of Yekaterinburg agglomeration) - Bazayeva Elena D.; Nadymov Ivan I. (Архитектон)
The article reveals modern prerequisites and aspects of integrated architectural and urban planning support for socio-biospheric development, the essence of which lies in the creation of a spatial physical environment based on specified parameters of socio-cultural development and interaction between natural and urbanized landscapes. The socio-biosphere derives from a comprehensive assessment of the design object across all of its infrastructures, introduction of socio-cultural content, techniques and methods of territorial development in the context of the identified architectural and urban planning aspects of interaction between the city and nature. The potential of socio-biospheric development is evaluated using Yekaterinburg agglomeration as an example. Conclusions are formulated on the possibility of further development of the concept based on architectural and landscaping regulation of the environment.